A comparative study of blood culture and immunochromatographic assay for rapid diagnosis of typhoid fever (Bangladesh Journal of Medical Microbiology, 2020)
Background and objectives: Typhoid fever, caused by Salmonella Typhi, is an important cause of morbidity and mortality in many developing countries including Bangladesh. As early diagnosis of disease and prompt treatment are essential for optimal management, a rapid method is urgently needed. Blood culture is the gold standard for diagnosis of typhoid fever, but it is time consuming. Immunochromatographic test (ICT) is easily accessible, cheap and simple method for diagnosis of typhoid fever, especially in the resource poor countries like Bangladesh.Methodology: 180 samples were collected from suspected typhoid fever cases. This study was conducted to isolate the S. Typhi by blood culture and to detect IgM and IgG antibody to S. Typhi by ICT method.Results: Out of 180 samples, 105(58.33%) were positive in ICT and 24(13.33%) were positive in blood culture. Considering blood culture as gold standard, the sensitivity, specificity, positive predictive value of ICT was 91.67%, 46.79%, 20.95% and 97.33% respectively.Bangladesh J Med Microbiol 2020; 14 (1): 7-10